2006
DOI: 10.2174/138955706778195144
|View full text |Cite
|
Sign up to set email alerts
|

Historical and Current Perspectives of Neuroactive Compounds Derived from Latin America

Abstract: Plants and invertebrates in Latin America have contributed to a great extent in the use, discovery and development of novel neuroactive tools. Significantly, these neuroactive drugs have proven to be particularly important for our current understanding of the physiology and pharmacology of the nervous system. In addition, these discoveries have helped to build the modern and successful pharmacological business that we know today. For example, curare helped to introduce the use of muscle relaxing agents into mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 115 publications
(137 reference statements)
0
5
0
Order By: Relevance
“…So while quinine is the active ingredient, it does not itself explain the process through which it works. There are many other examples in medicine in which (1) organic compounds are found to affect behavior, (2) the active ingredient is then isolated, and (3) subsequent understanding of its mechanism of action leads to the development of additional therapeutic agents (Aguayo et al, 2006; Tagboto and Townson, 2001). Research on psychological interventions achieved step 1 via recent work on the development of evidence‐based treatments; however, more attention is needed to steps 2 and 3.…”
Section: Evaluating Mechanisms Of Change In Psychological Treatmentsmentioning
confidence: 99%
“…So while quinine is the active ingredient, it does not itself explain the process through which it works. There are many other examples in medicine in which (1) organic compounds are found to affect behavior, (2) the active ingredient is then isolated, and (3) subsequent understanding of its mechanism of action leads to the development of additional therapeutic agents (Aguayo et al, 2006; Tagboto and Townson, 2001). Research on psychological interventions achieved step 1 via recent work on the development of evidence‐based treatments; however, more attention is needed to steps 2 and 3.…”
Section: Evaluating Mechanisms Of Change In Psychological Treatmentsmentioning
confidence: 99%
“…In parallel, the immunocytochemistry results showed that HaTX induced synaptic disconnection to the same extent as TTX, suggesting that the acute neurotoxicity induced by both toxins involves a synaptic disorganization that affects synaptic activities and neurotransmission (Zhang and Lisman, 2011). Taken together, this work suggests that H. akashiwo is capable of producing compounds that can inhibit neuronal VDSCs, like TTX, and are more closely related to brevenals, classical sodium channel blockers (Aguayo et al, 2006).…”
Section: Discussionmentioning
confidence: 57%
“…1), discarding any effect associated to the in vivo production of glycocalyx analogs. On the other hand, H. akashiwo has been classically associated to the production of neurotoxins similar to brevetoxins (Khan et al, 1997), long lipophilic polyether chains (10-11 rings) characterized by their excitotoxic properties that are related with the opening of voltage dependent sodium channels (Aguayo et al, 2006;Dechraoui et al, 1999;Lombet et al, 1987). However, under our experimental conditions, HaTX exhibited more of an inhibitory rather than excitatory effect as demonstrated by our data with A. salina and N2A cells using the neuroblastoma Neuro2a cytotoxicity assay (1 h; 25 nM) treated neurons using antibodies against PSD95 (green) and MAP-2 (red).…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) recognizes the importance of medicinal plants in the treatment and prevention of several diseases, as well as their economic relevance since they are a potential source for new drugs that may have a much lower cost. Considering that several compounds present in plants are highly potent and selective 8 , it is interesting to focus efforts to obtain new active ingredients that provide alternative approaches for the development of drugs to treat different diseases. To date, a wide range of dietary factors have been associated with preventing the development of prostate cancer, including genistein from soybeans 9 , flavonolignans 10 , vitamin C and E 11,12 , selenium 13 and zinc 14 .…”
Section: Anti-proliferative Effect Of Terpenes On Human Prostate Cancmentioning
confidence: 99%